2017
DOI: 10.1177/1744806916688219
|View full text |Cite
|
Sign up to set email alerts
|

Glial activation in the collagenase model of nociception associated with osteoarthritis

Abstract: BackgroundExperimental osteoarthritis entails neuropathic-like changes in dorsal root ganglia (DRG) neurons. Since glial activation has emerged as a key player in nociception, being reported in numerous models of neuropathic pain, we aimed at evaluating if glial cell activation may also occur in the DRG and spinal cord of rats with osteoarthritis induced by intra-articular injection of collagenase.MethodsOsteoarthritis was induced by two injections, separated by three days, of 500 U of type II collagenase into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…Moreover, neuron-glia interactions play a role in the chronic phase. Consistent with previous studies in monoarthritis or osteoarthritis [13,14], our RA mice showed increased number of SGCs. With TDAG8 deficiency, the increased number of SGCs was completely inhibited.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, neuron-glia interactions play a role in the chronic phase. Consistent with previous studies in monoarthritis or osteoarthritis [13,14], our RA mice showed increased number of SGCs. With TDAG8 deficiency, the increased number of SGCs was completely inhibited.…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that polyarthritis occurred in RA mice. In a monoarthritis model or collagenase arthritis model, arthritic rats showed SGC proliferation and activation [13,14]. To determine whether the number of SGCs was also increased in our RA mice, DRG from RA mice were immunostained for anti-GFAP (a SGC marker).…”
Section: Ra Mice Display Increased Number Of Sgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another CatWalk ™ study revealed abnormal coordination and intensity data after intraplantar CFA injection [43]. In similar adjuvant-induced mono-arthritis models, CatWalk ™ revealed abnormal gait data [4454], and the intensity data were highly correlated with punctate allodynia and knee-bend score [55]. Moreover, all gait parameters were partially improved by analgesic therapies [45, 48, 50].…”
Section: Discussionmentioning
confidence: 99%
“…The acute intrathecal injection aimed at reaching the lumbar spinal segments and was performed according to our protocol (Adaes et al, ) which was adapted from (De la Calle & Paino, ; Ossipov, Suarez, & Spaulding, ). Briefly, rats were anesthetized with isoflurane as described above and the rats’ abdomen‐pelvic region was lifted to create a slight curvature in the vertebral column at vertebral level L5–S1, which was localized using the anterior part of the iliac crest as a tactile reference point for the L6 vertebra.…”
Section: Methodsmentioning
confidence: 99%